2018
DOI: 10.1101/440396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional clustering of dendritic activity during decision-making

Abstract: The active properties of dendrites support local nonlinear operations, but previous imaging and electrophysiological measurements have produced conflicting views regarding the prevalence of local nonlinearities in vivo. We imaged calcium signals in pyramidal cell dendrites in the motor cortex of mice performing a tactile decision task. A custom microscope allowed us to image the soma and up to 300 µm of contiguous dendrite at 15 Hz, while resolving individual spines. New analysis methods were used to estimate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 101 publications
4
20
0
Order By: Relevance
“…These observations motivated the idea of functional synaptic clustering: to elicit dendritic spikes, inputs showing correlated in vivo activity should target nearby dendritic locations (Larkum & Nevian, 2008). Consistent with this idea, in vivo imaging of the activity of dendritic spines demonstrated that neighbouring synapses are co-activated more often than random (Takahashi et al, 2012;Winnubst et al, 2015;Iacaruso et al, 2017;Scholl et al, 2017;Kerlin et al, 2018) suggesting the involvement of active processes in the formation of functional clusters. However, both the relative importance of synaptic clustering compared to other factors influencing neuronal responses under in vivo conditions and the biophysical mechanisms leading to their formation are unknown.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…These observations motivated the idea of functional synaptic clustering: to elicit dendritic spikes, inputs showing correlated in vivo activity should target nearby dendritic locations (Larkum & Nevian, 2008). Consistent with this idea, in vivo imaging of the activity of dendritic spines demonstrated that neighbouring synapses are co-activated more often than random (Takahashi et al, 2012;Winnubst et al, 2015;Iacaruso et al, 2017;Scholl et al, 2017;Kerlin et al, 2018) suggesting the involvement of active processes in the formation of functional clusters. However, both the relative importance of synaptic clustering compared to other factors influencing neuronal responses under in vivo conditions and the biophysical mechanisms leading to their formation are unknown.…”
Section: Introductionmentioning
confidence: 64%
“…In particular, the spatial scale of the synapses showing correlated activity in vivo has been found to be restricted to 5-10 µm and involved a small number, ∼2-5 dendritic spines (Takahashi et al, 2012;Iacaruso et al, 2017;Scholl et al, 2017;Kerlin et al, 2018). This is substantially less than the 10-20 inputs required to trigger dendritic spikes under in vitro conditions (Mel, 1993;Losonczy & Magee, 2006;Makara & Magee, 2013;Branco & Häusser, 2011) leaving the potential impact of the clusters elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite functional synaptic clustering in the developing hippocampus (1)(2)(3)8) , no such fine-scale spatial organization was initially observed in the mature sensory cortex (12)(13)(14)16) . The emerging evidence now points to species-specificity of synaptic clustering for different stimulus features (6,7,9,10) . To reconcile these findings, we developed a unifying computational framework for the emergence of both local and global synaptic input organization on cortical dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The transient, precise synchronization of even a small group of synapses can result in the nonlinear summation of synaptic activity (62) , enhancing a neuron's computational capacity (18) (however, see refs. (9,63) ). These nonlinearities can counteract location-dependent gradients of conductances across synapses, effectively establishing a synaptic democracy (9,64) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation